Seed handling in genebanks: Self-learning module - Rao, N.K.; Hanson, J.; Dulloo, Mohammad Ehsan; Goldberg, E. (2006)
English version French version Spanish version This interactive self-learning module on seed handling in genebanks is drawn from the Handbook for genebanks no. 8: Manual of seed handling in genebanks (RAO et al., 2006). This is the standard reference for genebank work and one of the few sources of practical information for genebank curators and technicians on seed conservation, technology, storage and management. Targeting genebank curators and technicians, as well as university students, Seed handling in genebanks: Self-learning module is an open-access on-line learning tool. It is organized into units and lessons according to the general sequence of work undertaken in genebanks. Each lesson is presented independently, however, so that users may begin at any lesson of interest. You can request a copy on CD-rom by sending an email to bio-kmcs @ cgiar.org